TOPIC: HOW TO IMPROVE 9 TH GRADE STUDENTS’ PRONUNCIATION SKILLS ESPECIALLY, COMBINATION OF LETTERS EFFECTIVELY? - Qodirova , Mavluda Rustamjon qizi (Educational Research in Universal Sciences, 2023)
How to improve students’ knowledge on pronunciation especially combination of letters is the problem of the research. In order to tackle the issue some ways were done based on pre while post actions. Firstly, students level of knowledge were checked by made them read English texts from the book. Then different rules were taught by the teacher and listened various samples of correct pronunciation. at the end of this research variety of exercises were takeb from the students to check their skills development on this theme. As a result, almost all students said that it worked and roughly their skills on combination of letters increased for 20%. When the teacher made the students read the text they made few mistakes compared to the previous mistakes. It means that in order to improve one side of second language teachers shouls try to improve it by using all the sections of the language, such as listening, reading as I used in this research.